Application of Ki Hajar Dewantara's Arts Education Concept through Art Therapy to Overcome Students' Moral Decadence - Maulida Fitri; Herman Nirwana; Dina Sukma (Manajia: Journal of Education and Management, 2024)
The aim of this research is to provide a reference for teachers and guidance counselors in overcoming the problem of students' decline in moral decadence through the Ki Hajar Dewantara arts education concept. To achieve this goal, this research uses literature or literature review methods. This research collects literature from various books and articles related to the subject discussed. The results of the research show that Ki Hajar Dewantara's concept of arts education is considered suitable for overcoming the problem of students' moral decadence. This is because art produces refinement and order. So that it can improve human values, through developing various aspects of the human self as a whole.  Apart from that, it can also develop aspects of children's thoughts, feelings and wills in a balanced way, so that they can develop into complete and happy individuals.